Mapeamento de variáveis tipológicas de segunda moradia em edifícios residenciais no litoral do Aquiraz, Ceará - Oliveira, Bruno Barbosa de (2014)
The union of the provision of infrastructure and the expansion of the engine results in higher frequency of trips to the settlements of second home located in the peripheral municipalities of Brazilian metropolitan regions (Arrais, 2013). The region of Porto das Dunas, located on the coast of the municipality of Aquiraz fits that profile, as is distant 26 km from the downtown of Fortaleza and has several projects second home. Thus, this paper aims to form a database with geometrical characteristics of architectural projects for multifamily residential buildings approved in the City of Aquiraz. To achieve this goal, it was a collection of data held within the Secretaria Municipal de Meio Ambiente e Desenvolvimento Urbano Aquiraz-Ce (SEMAD). These data include basic geometric characteristics of the buildings, such as pavement type area, private area of units, floor area environments, environments and perimeter compactness index of the pavement. Moreover, it was analyzed the internal configuration of private units, where it was observed, among other things, the ratio of areas and dimensions of the rooms and the furniture perimeter of the kitchen. After obtaining the data, these are organized into spreadsheets and graphs generated using linear regressions over variables. Thus, it is intended, from the correlation of information gathered in the field, define the typical types of residential buildings of second home coastal Aquiraz-Ce and contribute for the improvement of new ventures in the same pattern for the region.